Induced plant volatiles and their effect on Spodoptera littoralis choice of host plant - Svensson, Thomas (2012)

(untitled)
Insects are the main pests of many crops despite many different control measures. There is a need for a better understanding of the factors that affect the relationship between insects and plants. It is important to investigate how insects find and choose their host plants. One factor affecting the relationship between insects and plants is plant-derived chemical cues. Many plants release increased levels of volatiles after insect herbivory. How the so-called induced volatiles affect the herbivore when it is about to oviposit is not well known. Avoidance of plants that release herbivore-induced plant volatiles in relation to oviposition have been found in some Lepidoptera species. Anderson & Alborn (1999) showed that females of Spodoptera littoralis choose to lay eggs on undamaged cotton plants, in two-choice test with damaged plants. In these bioassays the females showed that they were able to discriminate between damaged and undamaged cotton plants, until 10 days after the herbivory was terminated. This study has investigated how the induced defence, in cotton and maize, respectively affect the pattern of oviposition in S. littoralis. Herbivory by S. littoralis larvae induce changes in female decision of oviposition on cotton plants. My bioassays in cotton showed that S. littoralis is affected by the induced defence: the females prefer to oviposit on undamaged plants over damaged plants. My bioassays in the maize variety Pactol showed partly the same pattern as in the cotton, while in the variety Delprim there was no response from the females to larval feeding. From the literature it is known that if herbivory by S. littoralis on maize is ceased, the emissions of the induced plant volatiles drop rapidly already 10 hours after the stop and the emissions of plant volatiles from damaged maize plants are reduced to almost zero until day 3 after the damage occurred. In comparison, the induced defence in cotton lasts longer than in maize. S. littoralis larvae faeces only made a difference in the bioassay with the ongoing damage on cotton, in the sense that the females oviposited more on the side with undamaged plants compared to the side with the ongoing damage. In the bioassays with the ceased herbivory, with the damaged leaves still left on the plants, there was no impact on choices of the females. In a bioassay with the dummy paper plants, the females did not oviposit. In this case, the females lacked at least one of the cues needed for oviposition on a plant, such as the odour and the contact with the texture of the leaves. It was obvious that the dummies did not fool S. littoralis of being a host plant good enough to oviposit on. It seems like the decision by the female on how many eggs to oviposit could be controlled at two levels. S. littoralis can control both the number of egg batches as well as the number of eggs per egg batch in their choice between different oviposition places; this was shown in the case with the maize variety Pactol.